Dose–response with stereotactic body radiotherapy for prostate cancer: A multi-institutional analysis of prostate-specific antigen kinetics and biochemical control. (January 2021) - Levin-Epstein, Rebecca G.; Jiang, Naomi Y.; Wang, Xiaoyan; Upadhyaya, Shrinivasa K.; Collins, Sean P.; Suy, Simeng; Aghdam, Nima; Mantz, Constantine; Katz, Alan J.; Miszczyk, Leszek; Napieralska, Aleksandra; Namysl-Kaletka, Agnieszka; et al.
Highlights: Dose-escalation was associated with greater prostate ablation and PSA decay. All dose groups in our study achieved median nPSAs of ≤0.2 ng/mL. Dose-escalation to 40/5, but not beyond, was associated with improved BCRFS. Rates of BCR were low across all dose groups, with 5-year BCRFS estimates of at least 93%. Abstract: Background and purpose: The optimal dose for prostate stereotactic body radiotherapy (SBRT) is still unknown. This study evaluated the dose–response relationships for prostate-specific antigen (PSA) decay and biochemical recurrence (BCR) among 4 SBRT dose regimens. Materials and methods: In 1908 men with low-risk (50.0%), favorable intermediate-risk (30.9%), and unfavorable intermediate-risk (19.1%) prostate cancer treated with prostate SBRT across 8 institutions from 2003 to 2018, we examined 4 regimens (35 Gy/5 fractions [35/5, n = 265, 13.4%], 36.25 Gy/5 fractions [36.25/5, n = 711, 37.3%], 40 Gy/5 fractions [40/5, n = 684, 35.8%], and 38 Gy/4 fractions [38/4, n = 257, 13.5%]). Between dose groups, we compared PSA decay slope, nadir PSA (nPSA), achievement of nPSA ≤0.2 and ≤0.5 ng/mL, and BCR-free survival (BCRFS). Results: Median follow-up was 72.3 months. Median nPSA was 0.01 ng/mL for 38/4, and 0.17–0.20 ng/mL for 5-fraction regimens ( p < 0.0001). The 38/4 cohort demonstrated the steepest PSA decay slope and greater odds of nPSA ≤0.2 ng/mL (both p < 0.0001 vs. all other regimens). BCR occurred in 6.25%, 6.75%, 3.95%, and 8.95% of men treated with 35/5, 36.25/5, 40/5, and 38/4, respectively ( p = 0.12), with the highest BCRFS after 40/5 (vs. 35/5 hazard ratio [HR] 0.49, p = 0.026; vs. 36.25/5 HR 0.42, p = 0.0005; vs. 38/4 HR 0.55, p = 0.037) including the entirety of follow-up, but not for 5-year BCRFS (≥93% for all regimens, p ≥ 0.21). Conclusion: Dose-escalation was associated with greater prostate ablation and PSA decay. Dose-escalation to 40/5, but not beyond, was associated with improved BCRFS. Biochemical control remains excellent, and prospective studies will provide clarity on the benefit of dose-escalation.